2022
DOI: 10.3389/fimmu.2022.982264
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cholesterol-rich lipid rafts to disrupt influenza A virus infection

Abstract: Influenza A virus (IAV) is widely disseminated across different species and can cause recurrent epidemics and severe pandemics in humans. During infection, IAV attaches to receptors that are predominantly located in cell membrane regions known as lipid rafts, which are highly enriched in cholesterol and sphingolipids. Following IAV entry into the host cell, uncoating, transcription, and replication of the viral genome occur, after which newly synthesized viral proteins and genomes are delivered to lipid rafts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 244 publications
0
13
0
Order By: Relevance
“…Mechanically, in addition to their potential anti-inflammatory effects, previous studies have demonstrated that statins could play multiple roles in the regulation of virus susceptibility. Statins can reduce cholesterol availability, disrupt lipid raft composition, alter membrane receptor assembly, and thus limit virus fusion and entry into host cells [ 46 ]. One study also demonstrated that statins reduced the replication of influenza H1N1 by blocking RhoA and LC3 lipidation localization and inducing actin filaments condensation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, in addition to their potential anti-inflammatory effects, previous studies have demonstrated that statins could play multiple roles in the regulation of virus susceptibility. Statins can reduce cholesterol availability, disrupt lipid raft composition, alter membrane receptor assembly, and thus limit virus fusion and entry into host cells [ 46 ]. One study also demonstrated that statins reduced the replication of influenza H1N1 by blocking RhoA and LC3 lipidation localization and inducing actin filaments condensation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lipid bilayer provides the membrane with fluidity and elasticity. Studying lipid rafts present on cell surface proteins can provide detailed information on their functionality, e.g., T‐cell signaling, treatment of viral infection, receptor‐mediated channel activity, and therapeutic targets for cancer (Bobkov & Semenova, 2022; Carletti et al., 2017; Codini et al., 2021; Gold & Reth, 2019; Li et al., 2022; Magee et al., 2002; Nagy et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While serving as a platform for cell communication, they increase the vulnerability of cells to pathogen invasion (19). Studies have shown that LR are crucial for many viruses to invade cells, such as Hepatitis C virus (20), Zika virus (21), and In uenza A virus (IAV) (22). In fact, the LR and its related signal molecules have recently become important targets and are rapidly being used to develop antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%